What is the impact of the ACE gene insertion/deletion (I/D) polymorphism on the clinical effectiveness and adverse events of ACE inhibitors? - Protocol of a systematic review - Steurer J; Puhan MA; Scharplatz M; Bachmann LM (BMC, 2004)
Abstract Background The Angiotensin Converting Enzyme (ACE) insertion/deletion (I/D) polymorphism has received much attention in pharmacogenetic research because observed variations in response to ACE inhibitors might be associated with this polymorphism. Pharmacogenetic testing raises the hope to individualise ACE inhibitor therapy in order to optimise its effectiveness and to reduce adverse effects for genetically different subgroups. However, the extent of its effect modification in patients treated with ACE inhibitors remains inconclusive. Therefore our objective is to quantify the effect modification of the insertion/deletion polymorphism of the angiotensin converting enzyme gene on any surrogate and clinically relevant parameters in patients with cardiovascular diseases, diabetes, renal transplantation and/or renal failure. Methods Systematic Review. We will perform literature searches in six electronic databases to identify randomised controlled trials comparing the effectiveness and occurrence of adverse events of ACE inhibitor therapy against placebo or any active treatment stratified by the I/D gene polymorphism. In addition, authors of trials, experts in pharmacogenetics and pharmaceutical companies will be contacted for further published or unpublished data. Hand searching will be accomplished by reviewing the reference lists of all included studies. The methodological quality of included papers will be assessed. Data analyses will be performed in clinically and methodologically cogent subgroups. The results of the quantitative assessment will be pooled statistically where appropriate to produce an estimate of the differences in the effect of ACE inhibitors observed between the three ACE genotypes. Discussion This protocol describes a strategy to quantify the effect modification of the ACE polymorphism on ACE inhibitors in relevant clinical domains using meta-epidemiological research methods. The results may provide evidence for the usefulness of pharmacogenetic testing for individualised ACE inhibitor therapy.